Search 75,118 tutors
FIND TUTORS

Levi B.'s Resources

Answers

I'm assuming that the original function is x = √(y), is this correct?   The only transformation is the multiplication by -1 giving the x = -√(y) equation.  When multiplying by -1, you basically flip the graph about the axis that is not directly multiplied by the -1.  It...

Answers

Using the quadratic equation: [-b ±√(b2-4ac)]/2a where a = 12, b = 10 and -3 = c.

Answers

For this equation, you would plug in x+9 everywhere you find the r in the original equation.  What you get is 4/3*π(x+9)3.  Expanding out the (x+9)3 term the equation comes to V= 4/3*π(x3+27x2+243x+729.  Hope this helps.   Correction made.  Gotta...